Theoretical Investigation for the Influence of Various Parameters on the Performance of a Novel Concentration-Based Solar Desalination System - Mohammed, Mokhtar; Janan, Mourad Taha (Advances in Technology Innovation, 2022)
This study aims to investigate the influence of various parameters on the freshwater yield and efficiency of a novel concentration-based solar desalination system. The system performance under the summer and winter climatic conditions of Rabat city, Morocco is evaluated. The design parameters are glass cover thickness, absorber basin thickness, brackish water mass, and absorber basin material. The climatic parameters are wind velocity, ambient temperature, and solar radiation. Numerical studies on different system parameters are done by examining the effect of system component parameters on the system performance. Through the MATLAB code, the equations for the freshwater yield and efficiency of the new system are constructed and solved. The results show that the system gives the best performance with 6 mm glass cover thickness, 2 mm absorber basin thickness, and 40 kg brackish water mass.